One‐pot synthesis of star‐block copolymers using double click reactions - Durmaz, Hakan; Dag, Aydan; Hizal, Alp; Hizal, Gurkan; Tunca, Umit (Wiley, 2008)
Abstract3‐Arm star‐block copolymers, (polystyrene‐b‐poly(methyl methacrylate))3, (PS‐b‐PMMA)3, and (polystyrene‐b‐poly(ethylene glycol))3, (PS‐b‐PEG)3, are prepared using double‐click reactions: Huisgen and Diels–Alder, with a one‐pot technique. PS and PMMA blocks with α‐anthracene‐ω‐azide‐ and α‐maleimide‐end‐groups, respectively, are achieved using suitable initiators in ATRP of styrene and MMA, respectively. However, PEG obtained from a commercial source is reacted with 3‐acetyl‐N‐(2‐hydroxyethyl)‐7‐oxabicyclo[2.2.1]hept‐5‐ene‐2‐carboxamide (7) to give furan‐protected maleimide‐end‐functionalized PEG. Finally, PS/PMMA and PS/PEG blocks are linked efficiently with trialkyne functional linking agent 1,1,1‐tris[4‐(2‐propynyloxy)phenyl]‐ethane 2 in the presence of CuBr/N,N,N′,N″,N″‐pentamethyldiethylenetriamine (PMDETA) at 120 °C for 48 h to give two samples of 3‐arm star‐block copolymers. The results of the peak splitting using a Gaussian deconvolution of the obtained GPC traces for (PS‐b‐PMMA)3 and (PS‐b‐PEG)3 displayed that the yields of target 3‐arm star‐block copolymers were found to be 88 and 82%, respectively. © Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 46: 7091–7100, 2008